2020
DOI: 10.1111/bjso.12361
|View full text |Cite
|
Sign up to set email alerts
|

Collective directional movement and the perception of social cohesion

Abstract: We argue that perceivers associate collective directional movementgroups moving from one place to the nextwith higher levels of social cohesion. Study 1 shows that pairs are rated as being more cohesive when described as engaging in directional movement compared to non-directional activities. Study 2 replicates this finding using film clips. Study 3 reveals that the proximity of directionally moving dyads is a better predictor of perceived cohesion than behavioural synchrony. Study 4 replicates the original fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A possible explanation for this pattern is that the four walkers were processed as a group by default , possibly due to the fact that they moved in close proximity to one another. Indeed, previous work has shown that in the context of social cohesion, proximity is a stronger cue than synchrony (Wilson & Mansour, 2020). On this view, our results indicate that individuals walking in close proximity to each other are processed as a group, but that this group percept breaks down when there is no synchrony.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this pattern is that the four walkers were processed as a group by default , possibly due to the fact that they moved in close proximity to one another. Indeed, previous work has shown that in the context of social cohesion, proximity is a stronger cue than synchrony (Wilson & Mansour, 2020). On this view, our results indicate that individuals walking in close proximity to each other are processed as a group, but that this group percept breaks down when there is no synchrony.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there is currently little evidence that common fate in and of itself influences social perception. To our knowledge, there is only one study so far that has investigated whether observers ascribe different social dynamics to groups moving in the same vs. different directions (Wilson & Mansour, 2020). However, 'collective movement' in that study was operationalized as moving synchronously in the same direction, in close proximity to each other.…”
Section: The Role Of Common Fate In Social Groupingmentioning
confidence: 99%
“…In other words, collective movement in Wilson & Manour (2020) combined common fate with synchrony and proximity. Moreover, when participants were presented with two dots that always moved in the same direction, but did so asynchronously and without maintaining close distance, social cohesion was rated only 2.36 out of 7 (Wilson & Mansour, 2020). While more research is needed, this suggests a potential imbalance between synchrony and common fate, with the former but not the latter having an important social function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is currently little evidence that common fate in and of itself influences social perception. To our knowledge, there is only one study so far that has investigated whether observers ascribe different social dynamics to groups moving in the same vs. different directions (Wilson & Mansour, 2020). However, 'collective movement' in that study was operationalized as moving synchronously in the same direction, in close proximity of each other.…”
Section: The Role Of Common Fate In Social Groupingmentioning
confidence: 99%
“…Physical or physiological synchrony has been shown to correlate with positive collective experience of art, such as music [9][10][11], dancing in clubs [12], or watching movies [13]. Moreover, coordinated movement or physical synchrony have been shown to yield positive mental and emotional outcomes, including building rapport and increasing inter-brain synchronisation [14], improved cooperation [15,16], team problem-solving performance [17,18] and a sense of community [19], as well as the perception of social cohesion and shared experience in crowds [20], especially the bonding and 'identity fusion' in gatherings such as parades or protests [21].…”
Section: Introductionmentioning
confidence: 99%